Caracterização imuno-histoquímica de células do infiltrado inflamatório e de citocinas pró e anti-inflamatórias nos carcinomas mamários caninos - Garrido, Eduardo [UNESP] (2015)
Inflammation is a critical component of tumor progression and its malignancy is correlated with the inflammatory response induced by cytokines and infiltrating leukocytes in the tumor site. This study aimed to characterize, by immunohistochemistry, the inflammatory infiltrate and pro- and anti-inflammatory cytokines in canine mammary carcinomas and determine the molecular identity of tumors in luminal A or B, C-erbB-2 or basal. For this, we made immunodetection of macrophages, lymphocytes (CD4, CD8, Treg), cytokines (MIF, IL-10, IL-4 and TGF-β and IFN-ɣ), further on c-erbB-2, estrogen receptor and progesterone receptor and evaluated the average of immunostainings through the T test and analysis of variance in the breast tissue with or without carcinomas. There was statistical difference (p <0.0001) between the control group and the group of animals with simple breast carcinoma in all parameters, an increase in average animal affected by cancer. When the split occurred by histological type, all antibodies showed differences with the control group (p <0.0001). Simple breast carcinoma (papillary and tubular) showed increased macrophage counts, T lymphocytes, T helper lymphocytes, regulatory T as well as increase in the immunostaining of the cytokines MIF, IL-10, IL-4 and TGF-β compared to control group. The solid breast carcinomas have had a decreased of macrophages and subsets of T lymphocytes and IFN-ɣ, IL-4 and TGF-β, possibly for less stimulation of the immune system as evasion mechanism. The macrophages and T CD4 + lymphocytes and IL-10 cytokine were prevalent in the tubular pattern. The canine mammary carcinomas have a cell profile and cytokines with pro-tumor action, favoring their growth and ...